An experimental analysis on the influence of fuel borne additives on the single cylinder diesel engine powered by Cymbopogon flexuosus biofuel. Issue 4 (August 2017) - Dhinesh, B.; Niruban Bharathi, R.; Isaac JoshuaRamesh Lalvani, J.; Parthasarathy, M.; Annamalai, K.
Abstract: Researchers all around the world are making strenuous efforts to find alternative fuel to ameliorate the problem of depletion of fossil fuel. we have identified a novel plant based biofuel, namely Cymbopogon flexuous biofuel. It has excellent fuel properties and is widely available in India and it seems to have the potential to make India self-sufficient in energy production. Cerium oxide nanoparticles were synthesized using sol–gel combustion methods. Their structural, morphological and elemental properties were studied with the help of XRD, SEM, TEM and EDS respectively. On volume basis, 20% raw Cymbopogon flexuous biofuel was blended with diesel fuel, and various proportions of Cerium oxide nanoparticles, namely C20-D80 + 10 ppm, C20-D80 + 20 ppm andC20-D80 + 30 ppm were prepared. The properties like density, kinematic viscosity, calorific value of the test fuel were measured as per ASTM standards and compared with those of diesel fuel. An experimental study of its performance, emission, and combustion behavior was conducted at varied load conditions at a constant speed of 1500 rpm. NOx and smoke emission was simultaneously reduced by 3% and 6.6% respectively as compared with biofuel blend. Due to higher thermal stability and oxygen buffer of Cerium oxide nanoparticle the brake thermal efficiency was higher by 4.76% and cylinder pressure and heat release rate was also higher. Highlights: A novel biofuel, Cymbopogon Flexuosus is used as an alternative energy source. Cerium nanoparticle synthesis and its properties were analyzed. C20-D80 + 10 ppm, C20-D80 + 20 ppm and C20-D80 + 30 ppm were prepared. Resulting in higher thermal efficiency and lower HC, CO, emission. Reduction of Oxides of nitrogen and smoke emission was higher for C20-D80 + 20 ppm.